Analysis of the Development of VR (Virtual Reality) Based Interactive Learning Media Assisted by MilleaLab to Improve Learning Outcomes on the Material of Free Fall Motion Class XI in SMA Bengkulu City - Sehli Harnisa (IJOEM: Indonesian Journal of E-learning and Multimedia, 2023)
The purpose of this research is to analyze the needs to find out how necessary the development of interactive learning media based on Virtual Reality assisted by millealab in physics lessons for students and teachers. The method used is a qualitative descriptive method. The instruments used in this research are observation sheets, interview sheets, and accompanied by documentation. Based on the results of the study, it was found that because the learning media used during the learning process was still simple such as printed books, power-points, and animated videos, which caused students to be less interested and feel bored with the lesson because, the media was less interesting. As a result, student learning outcomes still need to be improved. Based on literature and field analysis that has been conducted in high schools, namely SMA Negeri 1 Bengkulu City, SMA Negeri 3 Bengkulu City, and SMA Negeri 9 Bengkulu City need or approve the development of interactive learning media based on Virtual Reality (VR) to improve the learning outcomes of high school students in physics subjects.